Bronchial Leech Infestation in a 15-Year-Old Female - Mohammad Ashkan Moslehi; Mohammad Hadi Imanieh; Ali Adib (Case Reports in Pediatrics)
Foreign body aspiration (FBA) is a common incidence in young children. Leeches are rarely reported as FBA at any age. This study describes a 15-year-old female who presented with hemoptysis, hematemesis, coughs, melena, and anemia seven months prior to admission. Chest X-ray showed a round hyperdensity in the right lower lobe. A chest computed tomography (CT) demonstrated an area of consolidation and surrounding ground glass opacities in the right lower lobe. Hematological investigations revealed anemia. Finally, bronchoscopy was performed and a 5 cm leech was found within the right B7-8 bronchus and removed by forceps and a Dormia basket.